Iterative finite element scheme for magnetoelectric energy harvesters - Nierla, Michael; Löffler, Michael; Rupitsch, Stefan (Procedia Engineering - Eurosensors 2015, 2015)
Magnetoelectric (ME) energy harvesting devices consisting of layered magnetostrictive/piezoelectric composites exploit the large mechanical strains arising from movements inside an external magnetic field to increase the electrical power output of the piezoelectric layers. Numerical methods help to optimize the design and the efficiency of such setups. Methods based on the solution of one directly coupled equation system, however, can in general not account for the change in geometry which occurs due to the harvester's movement inside the external magnetic field. In this contribution, we present an iteratively coupled Finite Element (FE) scheme for such devices that does not only enable the coupled simulation of magnetostrictive and piezoelectric effects, but furthermore allows the consideration of changing geometrie
Keywords: Energy Harvesting; Magnetostriction; Piezoelectricity; Finite Element Method; Iterative Coupling